Effects of facades positioned at different angles on building thermal performance and flow behaviors - Majid Amani-Beni; Mahdi Tabatabaei Malazi; Besir Sahin; Ahmet Selim Dalkılıç (Frontiers of Architectural Research)
This study simulates wind effects on a standard tall building model as specified by the Commonwealth Advisory Aeronautical Council (CAARC). We generated data to enhance living conditions through passive flow control, which mitigates building weathering, reduces wind loads, and improves energy efficiency and natural ventilation. The research also aids building designers with robust numerical predictions. The validity of these results was confirmed by comparing drag coefficient (CD) values with those from previous studies. The findings demonstrate that passive flow control significantly reduces wind-induced drag forces on the building at various angles of attack (α) by altering wind-induced pressures, reducing vorticity, and decreasing vortex shedding magnitudes. The objective was to identify the optimal placement of segmented cladding materials with desired gaps between segments to allow airflow to influence temperature variations when exposed to wind at 293 K and a heat flux of 500 W/m2 at wind speeds of 1, 2, and 4 m/s (Reynolds numbers of 5.2 × 10³, 10.4 × 10³, and 20.8 × 10³). Using 2D numerical analysis, twenty-four different facade and building model combinations were simulated. This study offers practical guidance on facade selection and positioning to optimize wind resistance and enhance the livability and functionality of building environments.